A Comparative Study of The Immunofluorescence in Brain, Salivary Gland and Cornea in Rabid Carcasses - Chandran, Divya; N., Vijayan; Nair, N. Divakaran; P., Suvaneeth (International Journal of Livestock Research, 2022)
The present study has compared the immunofluorescence observed in the brain, cornea, and salivary gland of rabid carcasses. It has enabled a relative assessment of the reliability, sensitivity, and effectiveness of using corneal and salivary gland impression smears for the diagnosis of rabies in live animals. The study was conducted on 352 carcasses belonging to various species of domestic and wild animals. Direct Fluorescent Antibody Test (dFAT) was performed on the brain of carcasses to detect rabies. The smear from the cornea and salivary gland of rabies-positive animals were also subjected to dFAT and a comparison was made between each with regard to the intensity of staining and the area of distribution as indicated by fluorescence. The study revealed that the sensitivity of corneal impression smear for rabies diagnosis in animals was found to be lesser when compared with impression smear from the salivary gland.